Choose MyPlate: Enjoy Your Food But Eat Less - Ashley Hamm; Karla P. Shelnutt; Gail P. A. Kauwell (EDIS)
Americans tend to select and consume larger portions than they need, and they don’t always make the best choices either. Part of the secret to maintaining a healthy diet is to know which foods to select and how to balance your intake with the amount of energy your body uses. This publication provides information about which foods make the healthiest contributions to our diets and which to limit. It also provides tips for making it easier to adjust your portions and to enjoy foods while making adjustments to your plate. This 4-page fact sheet was written by Ashley Hamm, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family Youth and Community Sciences, November 2013. http://edis.ifas.ufl.edu/fy1400